WILLIAM EDWARD DEMING'S MODEL PLANNING - Mey Mayangsari; Nur Ulwiyah; Uswatun Qoyyimah (Edusoshum : Journal of Islamic Education and Social Humanities, 2023)
The study of Total Quality Management (TQM) according to William Edward Deming's perspective is very important to carry out in order to find theoretical constructions for the application of Total Quality Management (TQM) in educational institutions. Implementation of Edward Deming's theory can be done by applying 14 points of management transformation. In an institution, especially education, planning is the main pioneer or spirit of the founding of an institution. This literature review of Edward Deming's planning model, apart from being widely used as references by institutions or companies in formulating programs, cannot be denied, also found several polemics that are important to study, starting from the Deming cycle, PDCA and PDSA. The purpose of this research is to find out William Edward Deming's planning model, especially in the field of education. This research uses a qualitative library research type approach. Data sources used as references in this research are books, websites, papers and scientific articles from various journals. The results of this research are that in general, William Edward Deming prioritizes anticipatory or preventive steps in quality improvement management. In line with that, it can be seen that Deming wants to convey that improving quality starts from the goal, making continuous improvements by focusing on education and training with the hope that activities run smoothly producing good quality.